Asymmetrical distribution of supports affect pea plants movement and shape: Evidence of quantity discrimination? - Silvia Guerra; Umberto Castiello; Valentina Simonetti; Bianca Bonato; Koleen McCrink (PLoS ONE)
The ability to discriminate more items from fewer items is an adaptive and innate cognitive feature of animals. Here, we found that this same capability is present in the plant kingdom. Pisum Sativum L. plants grew in the presence of supports that were distributed either equally (2 vs. 2; i.e., ED) or unequally (1 vs. 3; i.e., UD) on each side of a pot. Results showed that pea plants were able to sense the distribution of items in the environment, and to modulate the morphology and the kinematics of their tendrils on the basis of the support distribution. These findings indicate that processes such as quantity discrimination are present in plants, and are not restricted to the animal kingdom.